Intracellular pH regulates ubiquitin-mediated degradation of the MAP kinase ERK3 - Chloé Tesnière; Fadia Boudghene-Stambouli; Marc Severin; Mallorie Poët; Laure Voisin; Muthulakshmi Ponniah; Mirela Pascariu; Eric Bonneil; Jean-François Trempe; Pierre Thibault; Laurent Counillon; Stine Falsig Pedersen; et al. (Proceedings of the National Academy of Sciences, 2025)
Intracellular pH (pHi) influences diverse cellular processes, including cell proliferation, metabolism, and migration, and is linked to metabolic diseases and cancer. Protonation alters protein charge and conformation, modulating different aspects of protein function. How pHi fluctuations are sensed by signaling proteins and translated into cellular responses remains incompletely understood. Here, we reveal that pHi plays a key role in regulating the stability of the mitogen-activated protein kinase Extracellular signal-regulated kinase 3 (ERK3). Intracellular acidification markedly increases the half-life of ERK3, whereas alkalinization accelerates its degradation. The pH-dependent regulation of ERK3 is rapid, reversible, and consistent across cell types. Mechanistically, we identified a region in the C-terminus of ERK3 that contains pH-sensing motifs. We further show by quantitative proteomics that short-term acidification or alkalinization globally affects the cellular proteome. Our findings underscore the critical role of pHi in ERK3 turnover and suggest a broader role for pH in regulating protein stability and cell signaling.